Presynaptic Disorders: Lambert-Eaton Myasthenic Syndrome and Botulism - Gable, Karissa L.; Massey, Janice M. (Seminars in Neurology, 2015)
Lambert-Eaton myasthenic syndrome (LEMS) and botulism are acquired presynaptic nerve terminal disorders of the neuromuscular junction. Lambert-Eaton myasthenic syndrome is an idiopathic or paraneoplastic autoimmune syndrome in which autoantibodies of the P/Q-type voltage-gated calcium channel play a role in decreasing the release of acetylcholine, resulting in clinical symptoms of skeletal muscle weakness, diminished reflexes, and autonomic symptoms. Paraneoplastic LEMS is most often associated with small cell lung cancer. Diagnosis is confirmed by positive serologic testing and electrophysiological studies, which display characteristic features of low compound muscle action potentials, a decrement at 3Hz repetitive nerve stimulation, and facilitation with exercise or high-frequency repetitive stimulation. Treatment involves cancer monitoring and treatment, 3,4-diaminopyridine, immunosuppressive medications, and acetylcholinesterase inhibitors. Botulism is another presynaptic disorder of neuromuscular transmission. Clinical features classically involve cranial and bulbar palsies followed by descending weakness of the limbs, respiratory failure, and autonomic dysfunction. Electrodiagnostic testing is important in the evaluation and diagnosis. Treatment is supportive, and administration of antitoxin is beneficial in selected cases.
Keywords: Lambert-Eaton myasthenic syndrome; paraneoplastic syndrome; voltage-gated P/Q calcium channels; botulism; botulinum toxin; paralysis; electrodiagnosis; neuromuscular transmission disorders